The Values of Pancasila in Electronic Banking Agreement - Famauri, Andi Tenri (Hasanuddin Law Review, 2019)
Pancasila as a state’s foundation (philosophische grondslag), its values have exist, inherent and predicted in daily life as a way of life; therefore the material of Pancasila in the form of these values is the Indonesian Nation itself. The research is a normative-legal research. The research approach uses a statute, historical and conceptual approaches. The results show that Pancasila as the State’s foundation (Philosophische Grondslag) is universal and open, especially in the life of nation; it can be used in all aspects of life. Changes in banking activities, from conventional to electronic banking (e-banking) cannot be avoided again. The elements of morality and good values in banking are much needed, because banks as financial institutions that manage public money as customers have a great responsibility must be accompanied by honesty and dedication as important elements in trust. Consider the foundation of business in the banking sector is trust. The principle of good faith is placed as super eminent principle in the agreement. It is based on the principle of good faith related with the behavior of someone that becomes a basis for the agreement to bind them (pacta sunt servanda). Thus, the basic values of Pancasila that emphasize fair and civilized humanity can be applied as part of the values that live in Indonesian peoples.